Confidence and knowledge of Brazilian physiotherapists and physiotherapy students in managing patellofemoral pain - Batista, Natanael P.; Bazett-Jones, David M.; Waiteman, Marina C. [UNESP] (Elsevier, 2025)
Background: Previous research has explored clinicians' knowledge and confidence in managing patellofemoral pain (PFP), highlighting gaps in alignment with current evidence. However, there is limited research on Brazilian clinicians and physiotherapy students in this context. Objectives: To evaluate the knowledge and confidence of Brazilian physiotherapists and physiotherapy students in managing PFP and identify barriers to accessing scientific resources. Design: Cross-sectional online survey study. Method: We electronically recruited Brazilian physiotherapists and physiotherapy students. The Qualtrics survey included Likert-based and open-ended questions on demographics, confidence in PFP management, and knowledge related to PFP diagnosis, risk factors, prognosis, and treatment. Responses were compared to current evidence, and between-group differences were analyzed. Results/findings: A total of 46 physiotherapists and 51 students participated. Most physiotherapists were confident in managing PFP, but students were not. While most physiotherapists (93.4%) and students (86.3%) correctly defined PFP, only physiotherapists aligned with evidence-based diagnostic criteria. Both groups identified quadriceps weakness as a PFP risk factor but incorrectly cited hip weakness and dynamic knee valgus. Both groups correctly endorsed hip and knee exercises, physical activity modification, and load management as treatment strategies; however, 63.1% of physiotherapists incorrectly recommend knee brace for pain relief. Participants reported barriers to accessing scientific resources, including language, access difficulties, and searching knowledge gaps. Conclusions: Brazilian physiotherapists reported high confidence and accurate knowledge in managing PFP, but still held inaccurate beliefs about its risk factors and prognosis. Physiotherapy students demonstrated a need for further education. Important barriers limit their ability to stay informed on current evidence.
Keywords: Anterior knee pain; Knee; Knowledge translation; Rehabilitation; Risk factors